2021
DOI: 10.1186/s12889-021-11616-9
|View full text |Cite
|
Sign up to set email alerts
|

Should international borders re-open? The impact of travel restrictions on COVID-19 importation risk

Abstract: Background Novel coronavirus disease (COVID-19) has spread across the world at an unprecedented pace, reaching over 200 countries and territories in less than three months. In response, many governments denied entry to travellers arriving from various countries affected by the virus. While several industries continue to experience economic losses due to the imposed interventions, it is unclear whether the different travel restrictions were successful in reducing COVID-19 importations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Real-time travel volume, the numbers of cases in the source countries, and the ability to detect cases (i.e., surveillance capacity) should be considered in estimating the risk of travel-associated COVID-19. Travel volume is obviously related to imported cases, and the number of cases and surveillance capacity combined reflect the true size of the pandemic in the source countries 7 . Although several studies have estimated importation risks 8 14 , none of these used real-time travel data.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time travel volume, the numbers of cases in the source countries, and the ability to detect cases (i.e., surveillance capacity) should be considered in estimating the risk of travel-associated COVID-19. Travel volume is obviously related to imported cases, and the number of cases and surveillance capacity combined reflect the true size of the pandemic in the source countries 7 . Although several studies have estimated importation risks 8 14 , none of these used real-time travel data.…”
Section: Introductionmentioning
confidence: 99%
“…In [36], it has been reported that this situation affects not only prospective international students, but also international students who are already in the host countries and are obligated to prove that they have sufficient resources to support themselves throughout their studies. (iii) Nations across the globe closed international borders to mitigate the outbreak [37]. Educational authorities across the world were asking their international students not to travel overseas, or even to return to their country of origin, as they may put themselves at high risk of getting infected.…”
Section: International Students Researchers and Staffmentioning
confidence: 99%
“…However, there remained many knowledge gaps and arguments about whether implementing border policies were useful in the overall epidemic control. To be specific, border restrictions were once identified effective in suppressing early COVID-19 epidemics [ 18 , 19 ], whereas they were considered ineffective in regions where there already existed severe community spreads [ [20] , [21] , [22] ], implicating that conclusions may vary in different timings of observations. In fact, since outbreaks usually precede the adoption of border policies, previous observational studies performing in relatively short-term (Ranged form 14–153 days.…”
Section: Introductionmentioning
confidence: 99%